Gas magnetron deposition of structured TiO₂ nanofilms - Dobrovolskiy, A.M.; Goncharov, A.A.; Kostin, E.G.; Frolova, E.K. (Вопросы атомной науки и техники, 2013)
The paper describes the peculiarities of deposition nano-sized titanium dioxide coatings in the cylindrical inverted gas magnetron. It is shown the influence of the main parameters magnetron sputtering, like as working gas pressure and temperature of substrate, on film grain size, porosity and optical properties of deposited TiO₂ nanofilms. The investigations were carried out with films up to 200 nm of thickness.